TEACHING WRITING A REPORT TEXT : A Case Study at SMPN 6 Cirebon - Murtiani, Sri (2011)
This thesis reports an investigation of the teaching writing a Report text under the 2006 English Curriculum which uses the genre based approach (GBA). This study used a qualitative research design, especially a case study in order to gain an in dept understanding of the situation and meaning in applying the teaching of writing a Report text and the investigation on the benefit and problems found by English teacher. This study used multiple data collection, such as (i) the ongoing class observation; (ii) the use of interviews; (iii) the collection of the questionnaires and (iv) the collection of students written texts. The investigation of this research study used the phases of BKOF (twice), modeling (once), joint construction (three times) and independent construction (once). The results indicate that the competence of students writing a report text developed. The evidence can be seen in their written texts made and the result of final draft, that only two students who got the score under the minimum criteria of achievement (KKM), while 36 students had passed the minimum criteria of achievement (KKM). Meanwhile data from questionnaires and interviews indicate that the teacher's problem in implementing the GBA are to do with the teaching of linguistic features, such as technical terms, grammar, content and graphic features. The data from the English teacher were consistent with the results of students' questionnaires, such as grammar (10); technical terms (17); grammar and technical terms (7) others (4). Data from questionnaire and interview indicate that the teacher' s problems in implementing the GBA are to do with the teaching of linguistic features. It is recommended that English teacher could use the results of this investigation as an enrichment to apply the teaching of writing within a big class in Indonesian context.